Memahami Istidraj di Era Kontemporer: Analisis QS. Al-An’am: 44 Perspektif Tafsir Al-Mishbah - Fawwaz Affansyah; Ahmad Nurrohim (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to examine the meaning of istidraj in QS. Al-An'am verse 44 based on the perspective of tafsir Al-Mishbah by M. Quraish Shihab, and relate it to the phenomenon of life in the contemporary era. This study is motivated by the widespread phenomenon of worldly pleasures that are often mistaken for blessings, even though it could be a form of hidden test. The method used is library research, by examining relevant classical and contemporary tafsir literature. The results showed that istidraj is a form of test from Allah in the form of sustenance and success that actually plunges a person into spiritual negligence. Tafsir Al-Mishbah emphasizes that istidraj is not only a phenomenon of the past, but applies throughout the ages. In conclusion, understanding istidraj is very important so that Muslims are not trapped in the illusion of worldly pleasures, and always increase gratitude and faith as a form of protection from these deceptions.